Effects of Food Additives and Preservatives on Processed Food - Neelam, Mall; Mishra, Sunita (Asian Journal of Science and Applied Technology, 2018)
Foods are substances or mixture of substances both solid and/or liquid, which are intended for human consumption or ingestion for their nutritional pleasurable benefits. Food additives are organic substances that are intentionally added to food in small quantities during production and processing to improve or maintain the quality of the processed foods. Food preservatives is a class of food additives that help to present food spoilage by preventing the growth of microorganism .The effectiveness of preserve foods were tested with two parameters such as pH value ,moisture content at the interval of 0 days ,5 days, 15 days, 25 days. Two types of methods are used to preserve i.e. traditional and modern method. Under the traditional method I use salting and sun drying method and under the modern method, Ultrasonication and microwave method are used .In ultrasonication method, Nano particle such as Titanium dioxide is use as a preservative. Result of processed foods on physico-chemicals showed that pH was reduced on 25th days and moisture content was reduced on 25th days. With the ever growing world population and the need to store and transport the food from one place to another where it is needed food preservation becomes necessary in order to increase its shelf life and maintain & improve the quality of processed foods .The most common food additives and preservatives used are sodium benzoate , sodium chloride, titanium dioxide .The aim of this review is to summarize current information about food additives and its effects and increase the shelf life of processed foods.